Good Masters: A Reply to Massimo Fusillo, Daniele Scalise, Filippo La Porta and Gianluigi Rossini - Pierpaolo Antonello (Between, 2013)
A final comment given by Pierpaolo Antonello, author of Dimenticare Pasolini.